Evaluation of Anti-proliferative and Antioxidant Potency of Ficus benghalensis Hydroalcoholic Bark Extract against Lung Cancer Cell Line-A549 - Althafar, Ziyad M. (Indian Journal of Pharmaceutical Education and Research, 2024)
Background and Aim: One of the most prevalent cancers worldwide is lung cancer with the second top fatality rate. The purpose of this work is to disclose the anti-proliferative ability of hydroalcoholic Ficus benghalensis bark extract against lung cancer cell line (A549). Materials and Methods: Antioxidant property of Ficus benghalensis bark extract was studied using α, α-diphenyl-β-picrylhydrazyl and Hydrogen Peroxide assays. The investigation of anti-proliferative property of Ficus benghalensis hydroalcoholic bark extract was carried out through tetrazolium salt-based cytotoxicity assay, cell viability assessment using trypan blue dye and morphometric analysis. The cytotoxic potency was analysed by propidium iodide staining, oxidative stress markers determination and expression of apoptotic gene markers such as Bax, c-MYC and PARP. Results: The anti-oxidant assays revealed the great radical scavenging property of Ficus benghalensis bark extract. Ficus benghalensis hydroalcoholic bark extract showed 50.12% inhibition at 50 μg/mL which is also confirmed by viability assay. In morphometric analysis the distortion of cells were noted in treated groups. The nuclear staining and gene expression studies further confirms the anti-cancer activity of Ficus benghalensis hydroalcoholic bark extract. The estimation of release of nitric oxide and lipid peroxidation was high in treated groups which also supports the previous results. Conclusion: The study emphasize the anti proliferative and anti oxidant property of Ficus benghalensis hydroalcoholic bark extract against A549 cell line
Keywords: Ficus benghalensis bark extract; Lung cancer cell line; Anti proliferation; Apoptosis; Oxidative stress; Anti-oxidant